Analysis of NOR distribution in cultivated and naturalized stocks of rainbow trout (Oncorhynchus mykiss) - Fábio Porto-Foresti; Claudio Oliveira; Yara A. Tabata; Marcos G. Rigolino; Fausto Foresti (Genetics and Molecular Biology, 2002)
In salmonid species, nucleolar organizing regions (NORs) have frequently been found on a single chromosome pair. However, some other, smaller yet active NORs have also been described. In the present study, NORs were found to be located in different positions on the chromosomes of 12 rainbow trout samples (11 cultivated and one naturalized stocks). Three phenotypes were found: 1) NORs located on two submetacentric chromosomes, in a subterminal position on the short arm (AA); 2) NORs located on two submetacentric chromosomes, in a subterminal position on the long arm (BB); and 3) NORs located on two submetacentric chromosomes, one in a subterminal position on the short arm, and the other in a subterminal position on the long arm (AB). Phenotype AA was identified in individuals from ten cultivated stocks, phenotype AB was identified in individuals from three cultivated stocks, and phenotype BB was found in one cultivated and one wild stock. Some aspects of the origin and the distribution of the different phenotypes are discussed.